2021
DOI: 10.1371/journal.pone.0259643
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiome affects the metabolism of metronidazole in mice through regulation of hepatic cytochromes P450 expression

Abstract: Microbiome is now considered as a significant metabolic organ with an immense potential to influence overall human health. A number of diseases that are associated with pharmacotherapy interventions was linked with altered gut microbiota. Moreover, it has been reported earlier that gut microbiome modulates the fate of more than 30 commonly used drugs and, vice versa, drugs have been shown to affect the composition of the gut microbiome. The molecular mechanisms of this mutual relationship, however, remain most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 36 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…Metronidazole is considered to have broad toxicological prospects compared to most xenobiotics due to its biotransformation in the liver through oxidation, hydroxylation, and conjugation of metronidazole glucuronide [17]. Moreover, a cumulative number of studies on animals and humans indicated an association of metronidazole with the disturbance of alanine aminotransaminase (ALT), aspartate aminotransaminase (AST), alkaline phosphatase (ALP), total cholesterol (TC), and triglyceride (TG), which are factors involved in hepatotoxicity [18].…”
Section: Introductionmentioning
confidence: 99%
“…Metronidazole is considered to have broad toxicological prospects compared to most xenobiotics due to its biotransformation in the liver through oxidation, hydroxylation, and conjugation of metronidazole glucuronide [17]. Moreover, a cumulative number of studies on animals and humans indicated an association of metronidazole with the disturbance of alanine aminotransaminase (ALT), aspartate aminotransaminase (AST), alkaline phosphatase (ALP), total cholesterol (TC), and triglyceride (TG), which are factors involved in hepatotoxicity [18].…”
Section: Introductionmentioning
confidence: 99%
“…Gut microbiota is not only an important agent during pathophysiological processes but it can also influence pharmacotherapy outcomes by affecting the biotransformation and pharmacokinetics of a wide range of clinically used drugs including the drugs used to treat IBD ( Jourova et al, 2016 ; Jourova et al, 2019 ; Zemanová et al, 2021 ). Moreover, the gut microbiome may also indirectly influence the level of drug-metabolizing enzymes through bacterial metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence shows that gut microbiota has a certain capacity of drug biotransformation with various consequences on the drug pharmacological activity [ 11 , 12 , 13 ]. Experiments on germ-free (GF) animals showed that gut microbiota and its metabolites are implicated in the regulation of expression of a host’s hepatic cytochromes P450 (CYPs) [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%